Training on improving and developing business opportunities for micro, small and medium enterprises (UMKM) through online promotions on social media in the building in kelurahan gedung Johor kecamatan Medan Johor - Aflah; Hasibuan, Puspa Melati; Herlinda, Erna; Syahriah, Rabiatul; Laksamana, Boy (Talenta Publisher, 2020)
Social media is a gathering place for people using internet networks, not infrequently even on social media people who have the same mutual interests and form a community. The presence of these community groups can certainly be a target for business people to promote their products, including products from MSMEs. Promotion through the community on social media can be done through soft selling. Effective and efficient use of social media by business actors as a means of trade promotion requires guidance and direction through training. Therefore, in this community service activity, training was carried out on improving and developing business opportunities for Micro, Small and Medium Enterprises (MSMEs) through online promotions on social media to MSMEs located in Kelurahan Gedung Johor. The method of implementing activities is carried out in the form of counseling and interactive dialogue with participants. The use of social media is carried out effectively by providing the best service to consumers by conveying honestly and in good faith, about the merchandise being promoted, there are no things to hide, this is useful for building the seller's reputation and maintaining the trust given by consumers so that consumers remain loyal to the merchandise products of these MSME entrepreneurs.